Computing wave solutions and conservation laws of conformable time-fractional Gardner and Benjamin-Ono equations - Singh, Sudhir; Sakthivel, R.; İnç, Mustafa; Yusuf, A.; Murugesan, K. (Indian Acad Sciences, 2021)
This paper presents travelling wave solutions for the nonlinear time-fractional Gardner and Benjamin-Ono equations via the exp(-Phi(epsilon))-expansion approach. Specifically, both the models are studied in the sense of conformable fractional derivative. The obtained travelling wave solutions are structured in rational, trigonometric (periodic solutions) and hyperbolic functions. Further, the investigation of symmetry analysis and nonlinear self-adjointness for the governing equations are discussed. The exact derived solutions could be very significant in elaborating physical aspects of real-world phenomena. We have 2D and 3D illustrations for free choices of the physical parameter to understand the physical explanation of the problems. Moreover, the underlying equations with conformable derivative have been investigated using the new conservation theorem.
Keywords: Gardner equations; Benjamin-Ono equation; exp expansion approach; conformable fractional derivative; periodic solutions; symmetry analysis; 11; 30; j; 05; 45; Yv; 02; 30; Jr